2021
DOI: 10.1051/bioconf/20212901001
|View full text |Cite
|
Sign up to set email alerts
|

Study of student’s self-isolation adaptation strategies during the Covid-19 pandemic

Abstract: The COVID-19 epidemic, which turned into a pandemic, has led to the introduction of lockdown in many countries as a measure to prevent the spread of the virus. Significant changes have occurred in the lives of Russian students. The research objective is to study students’ strategies of adaptation to the self-isolation caused by the need to prevent the spread of COVID-19. To achieve this purpose, an online survey of students was conducted, followed by a correlation analysis of the data. The survey involved 269 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Other personal strategies reported include receiving support from family and friends, recreational activities, independence, humor, and religion (36). As an additional strategy, students use behaviors that are intended to change conditions and to confront others (environmental change) (37). Further, many studies have shown that students use new coping strategies such as being tolerant of situations, using social media, exercising, taking advantage of attention or self-distraction, beliefs and spirituality, and being altruistic (38).…”
Section: Discussionmentioning
confidence: 99%
“…Other personal strategies reported include receiving support from family and friends, recreational activities, independence, humor, and religion (36). As an additional strategy, students use behaviors that are intended to change conditions and to confront others (environmental change) (37). Further, many studies have shown that students use new coping strategies such as being tolerant of situations, using social media, exercising, taking advantage of attention or self-distraction, beliefs and spirituality, and being altruistic (38).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interventions by some schools and state governments to bridge the gap created by COVID-19 to students' learning, some students may still be unable to learn. Carr et al (2020), cited in Sivrikova et al (2021), remarked that people experienced future uncertainties, boredom, anxiety for death, disappointments, and frustrations owing to unmet expectations during the COVID-19 lockdown. Some students may have difficulties coping with the online education introduced by some higher institutions, owing to the challenges characterized by digital learning.…”
Section: Open Accessmentioning
confidence: 99%